A abordagem didático-investigativa no ensino médio: um estudo acerca do DNA - Kassiana da Silva Miguel; Iasmine Alessandra Oliveira Baracho Campos; Carla Milene Knechtel; Daniela Frigo Ferraz; Lourdes Aparecida Della Justina (Universidade Estadual de Campinas, 2014)
This paper is a result of a research performed in the context of the program of scholarships for beginner teachers, from the ubproject of Biological Sciences in a public university of Paraná. The goal was to highlight the reconstruction of the concept of the DNA during the development of a courseware module in a investigative focus with students from the third year of high school of a public school of Paraná. There was a systematic monitoring and data gathering through several instruments. The analysis was organized in four different moments: hypothesis development by the students, the development of drawings about DNA, research performed by the students on the concept of DNA and individual descriptive synthesis. Through the analysis of the results it could be emphasized that the investigative focus allowed the active participation of the students, especially in the class questionings and synthesis development. We highlight also that there was evidences as to the reconstruction of the DNA concept by the students involved.